Silver‐Catalyzed Functionalization of Esters by Carbene Transfer: The Role of Ylide Zwitterionic Intermediates. Issue 8 (2nd July 2014) - Gava, Riccardo; Fuentes, M. Ángeles; Besora, Maria; Belderrain, Tomás R.; Jacob, Kane; Maseras, Feliu; Etienne, Michel; Caballero, Ana; Pérez, Pedro J.
Abstract The reaction of esters with ethyl diazoacetate catalyzed by the complex [F27–Tp<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghwkxqm7m" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> 4 Bo, 3 CF 2CF 3</alternatives>Ag(acetone)] generates α‐(acyloxy)acetates in moderate to high yields. This is a novel transformation in the context of carbene‐transfer reactions from diazo compounds that, according to experimental and theoretical data, is suggested to occur through zwitterionic intermediates.